2018
DOI: 10.1111/psyg.12322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olfactory stimulation on reminiscence practice in community‐dwelling elderly individuals

Abstract: The results suggest that reminiscence intervention using olfactory stimulation may maintain the mental health of community-dwelling elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…RT was carried out in a group setting, which is the most recommended by different researchers ( Watt and Cappeliez, 2000 ; Westerhof et al, 2004 ; Karimi et al, 2010 ; Haslam et al, 2014 ; Smiraglia, 2015 ; Soniya, 2015 ; Lopes et al, 2016 ; Hanaoka et al, 2018 ; Satorres et al, 2018 ; Siverova and Buzgova, 2018 ). The intervention consists of a reminiscence program, directed by a psychologist.…”
Section: Methodsmentioning
confidence: 99%
“…RT was carried out in a group setting, which is the most recommended by different researchers ( Watt and Cappeliez, 2000 ; Westerhof et al, 2004 ; Karimi et al, 2010 ; Haslam et al, 2014 ; Smiraglia, 2015 ; Soniya, 2015 ; Lopes et al, 2016 ; Hanaoka et al, 2018 ; Satorres et al, 2018 ; Siverova and Buzgova, 2018 ). The intervention consists of a reminiscence program, directed by a psychologist.…”
Section: Methodsmentioning
confidence: 99%
“…61 Hanaoka et al reported that olfactory stimulation for reminiscence practice, which is the volitional or non-volitional act or process of recollecting memories of individual episodes, was a useful intervention for maintaining mental health, although the effect of reminiscence on cognitive function was not shown in this study because of the ceiling effect of the Mini-Mental State Examination and the time-dependent manner reported previously. 62,63 In mild cognitive impairment and early dementia, cognitive function and psychiatric symptoms, such as motivation and depression, which are associated with frontal lobe function, often interact and accompany mutually. A recent study in rats showed that formation of permanent memories over time required the generation of new prefrontal engram cells that are formed at the same time as the initial memory cells in the hippocampus, as well as neuronal connections in the cerebral cortex, particularly the prefrontal cortex.…”
Section: Aromatherapy For Cognitive Decline and Dementiamentioning
confidence: 99%
“…At this moment, whether the neural correlates of nostalgia differ depending on the memory content (e.g., people, object, and places) and memory type (e.g., episodic and semantic AM) is still not fully understood. Investigation of the mechanisms underlying individual differences in nostalgia functions would provide neuroscientific evidence for applications, especially in clinical settings such as reminiscence therapy for individuals with dementia (Hanaoka et al, 2018;Istvandity, 2017;Yasuda et al, 2009), depression (Hsieh & Wang, 2003), or terminal illness (Wholihan, 1992). Because the neuroimaging studies have largely focused on young populations, it is also important to validate the multilevel memory-reward coactivation framework in elderly people.…”
Section: Future Directions In Nostalgia Research and Application Of Nostalgia Experiencesmentioning
confidence: 99%